2009
DOI: 10.1111/j.1365-2044.2008.05852.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes for cancellation of elective surgical procedures in a Spanish general hospital

Abstract: SummaryCancellation of scheduled surgery is undesirable for patients and an inefficient use of resources. We prospectively collected data for 52 consecutive months in a public general hospital to estimate the prevalence and causes. The overall cancellation rate was 6.5% (2559 of 39 115 scheduled operations). Cancellation by broad category was for 'medical reasons' in 50%, 'patient-related factors' in 23%, and due to 'administrative ⁄ logistic problems' in 25%. The commonest specific causes within these categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 24 publications
7
74
3
7
Order By: Relevance
“…12 After a previous successful effort at CCHMC to reduce staff overtime costs by improving on-time day start and finish times, 13 DoSC was selected for improvement. Although cancelation is more common for children than for adults, 14 few studies describe the problem. [15][16][17][18][19] Fewer still report alleviating it.…”
Section: Figurementioning
confidence: 99%
“…12 After a previous successful effort at CCHMC to reduce staff overtime costs by improving on-time day start and finish times, 13 DoSC was selected for improvement. Although cancelation is more common for children than for adults, 14 few studies describe the problem. [15][16][17][18][19] Fewer still report alleviating it.…”
Section: Figurementioning
confidence: 99%
“…Ó 2011 by American Society of PeriAnesthesia Nurses SURGICAL CANCELLATIONS CAUSE distress and inconvenience to families, [1][2][3][4] interfere with operating room (OR) efficiency, 1,5 and add to the overall cost of care delivery. 1,2,6 Studies show that preoperative assessment clinic (POAC) evaluation of patients before elective surgery is effective in decreasing OR cancellations.…”
mentioning
confidence: 99%
“…1,2,6 Studies show that preoperative assessment clinic (POAC) evaluation of patients before elective surgery is effective in decreasing OR cancellations. 3,[6][7][8][9][10] There is little in the literature relating to pediatric elective surgery cancellations 2,5,9 or the role of nursing in the prevention of cancellations. 10,11 Most studies reviewed originated outside the United States [1][2][3][4][5]9,10 and were focused on dayof-surgery (DOS) cancellations, with the exception of two studies that also examined the time period between the preoperative evaluation and the DOS.…”
mentioning
confidence: 99%
“…Unexpected surgical cancellations are not uncommon, decrease patient satisfaction, waste medical resources, and undermine the morale of medical personnel [1][2][3][4]. Before seeking a strategy to reduce case cancellation rate, many medical providers and institutes investigate the cancellation rate and understand cancellation reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Before seeking a strategy to reduce case cancellation rate, many medical providers and institutes investigate the cancellation rate and understand cancellation reasons. Due to a lack of standard case cancellation definition, and using different study methods [1][2][3][4][5], studies in the US have reported cancellation rates from as low as 0.21% [6] to as high as 26% [7]. Cancellation reasons also vary across studies including medical condition changes, patient no show, and scheduling issues.…”
Section: Introductionmentioning
confidence: 99%